تحليل أسئلة امتحانات الشّهادة الثّانويّة العامّة لمادة اللغة العربيّة وفق مستويات بلوم المعرفيّة / The Analysis of General Secondary Examination (GSE) questions of Arabic language subject according to Bloom’s cognitive levels - بني ياسين محمّد فوزي أحمد (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2016)
ملخّص البحث: تهدف هذه الدّراسة إلى تحليل أسئلة امتحانات الشّهادة الثّانويّة العامّة لمبحث اللغة العربيّة في الأردنّ وفق مستويات بلوم المعرفيّة؛ للوقوف على مدى مناسبة أسئلة امتحانات الشّهادة الثّانويّة العامّة للأهداف الّتي وضعت من أجلها. وقد أظهرت نتائج التّحليل الآتي: بلغ عدد الأسئلة لمبحث اللغة العربيّة للسنوات 2010 – 2014 م بدورتيها الصّيفية والشتوية هو ) 318 ( سؤالاً، وأن جميع الأسئلة الوزارية بدورتيها الصّيفية والشتوية تركّز على أسئلة مستوى الفهم بنسبة عالية؛ حيث بلغت أعلى نسبة لها ) 50 %(، بينما كانت أدني نسبة لها ( 24.1 %(؛ أمّا أسئلة التّذكّر فقد بلغت أعلى نسبة لها ) 19.4 %(، بينما بلغت أدنى نسبة لها ) 10.3 %(؛ أمّا أسئلة التّطبيق فقد تفاوتت نسبها بين المرتفع والمتوسط؛ حيث بلغت أعلى نسبة لها ) 44.8 %( وأدنى نسبة لها ( 20.6 %(؛ ويلاحظ في أسئلة مستوى التّحليل تفاوتٌ بين أعلى نسبة لها؛ حيث بلغت ) 12.1 %( بينما بلغت أدنى نسبة لها ) 2.7 %( أما أسئلة مستوى التّّكيب فقد انخفضت نسبها في جميع السّنوات بدورتيها الشّتويّة والصّيفيّة؛ حيث بلغت أعلى نسبة لها ) 3.5 %( وأدنى نسبة لها ) 2.7 %(، أما أسئلة مستوى التّقويم فانعدمت فيها نهائياً، وكانت بنسبة )صفر%(. وخلصت الدّراسة إلى مجموعة من التّوصيات. الكلمات المفتاحيّة: تحليل الأسئلة - تقييم الأسئلة - الصّف الثّاني الثّانويّ المجال المعرفي بلوم. - - Abstract: The aim of this study is to analyze the General Secondary examination (GSE) questions of Arabic language subject in Jordan according to Bloom’s cognitive levels in order to assess the appropriateness of GSE examinations to the objectives which they were prescribed for. The results of the study show that: The number of questions of Arabic language subject for the years 2010 - 2014 in summer and winter session was (318) questions. All ministerial questions in summer and winter sessions focused mainly on the level of understanding with the highest rate of 50% and the lowest rate of (24.1%). Questions related to the level of remembrance reached the rate of (19.4%), while their lowest rate was (10.3%). As for questions related to the level of application, the percentage varied between high and medium, reaching the highest rate of (44.8%) while the lowest was (20.6%). Analysis questions showed a significant difference between the highest rate of (12.1%) and the lowest rate of (2.7%). The rate of questions related to structuring has decreased in all the years in winter and summer sessions reaching the highest rate of (3.5%) and the lowest rate of (2.7%). Furthermore, the assessment questions have been neglected with no percentage (0%). The study also suggests a set of recommendations. Key words: question analysis - question evaluation - the second secondary class - knowledge domain –Bloom. Abstrak: Kajian ini bertujuan untuk menganalisa soalan Peperiksaan Menengah Am matapelajaran Bahasa Arab in Jordan mengikut tahap pengetahuan taksonomi Bloom untuk menilai kesesuaian soalan-soalan peperiksaan tersebut mengikut objektif yang telah ditetapkan. Hasil kajian menunjukkan: Jumlah soalan-soalan untuk matapelajaran Bahasa Arab untuk tahun-tahun 2010 sehingga 2014 termasuk persekolah musim sejuk berjumlah 318 soalan keseluruhannya. Semua soalan peringkat Kementerian di musim panas dan sejuk kebanyakannya memfokus kepada peringkat pemahaman dengan peratusan sebanyak 50% dengan kadar terendah 24.1%. Soalan-soalan berkaitan tahap mengingati mencapai 19.4% manakala yang terendah ialah 10.3%. Soalan tahap applikasi pula terdapat variasi antara sederhana dan tinggi diantara 44.8% dan yang terendah ialah 20.6%. Soalan berbentuk analisa pula mencatat perezaan ketara di antara 12.1% dan 2.7%. Soalan berkenaan dengan pembentukan idea telah berkurangan dalam tempoh tersebut dalam sesi-sesi musim lanas dan sejuk dengan peratusan hanya 3.5% dan 2.7%. Soalan berbentuk penilaian pula tidak terdapat langsung (0%). Kajian ini seterusnya merumuskan beberapa cadangan. Katakunci: Analisa soalan - penilaian soalan - kelas menengah - domain pengetahuan – Bloom.